Hadith #5270 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Usayd Malik bin Rabi'a; al-Hakm bin Nafi', Abu al-Yaman الحكم بن نافع أبو اليمان الحمصي; Hamza bin Abi Usayd al-Sa'idi; Shdad bin Abi 'Amr شداد بن أبي عمرو بن حماس (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited throwing pebbles (in sport) saying : game is not caught by such means. Neither is an enemy injured, but it may sometimes put out an eye or break a tooth.
Grade: Sahih